RELATIONSHIP OF EMOTIONAL INTELLIGENCE AND HEALTH LOCUS OF CONTROL AMONG FEMALE BREAST CANCER PATIENTS IN PAKISTAN: Emotional Intelligence Female Breast Cancer - Naz, Rubina; Kamal, Anila; Mahmood, Ahsan (Pakistan Armed Forces Medical Journal, 2016)
Objective: To investigate relationship between emotional intelligence and health locus of control in married women with breast cancer disease. Study Design: Cross sectional study. Place and Duration of Study: The data was collected from Nuclear Oncology & Radiology Institute (NORI Hospital) Islamabad (n=210) and from Combined Military Hospital (CMH) Rawalpindi (n=101). Data collection was completed between the period from Oct 2013 to Feb 2014. Patients and Methods: The sample was selected using non- probability sampling technique. Collected breast cancer patients sample was n= 311 whose age range was from 18-80 years. A biographical sheet that contain personal and disease information of patient, and two scales were used: Self Report Measure of Emotional Intelligence (Khan & Kamal, 2010), and Multidimensional Health Locus of Control (Wallston, Stein, & Smith, 1994) were used to assess the constructs explored in this study. Results: Results depict that there was significant positive correlation between emotional intelligence (EI), including its sub scales Emotional Self-Regulation Skills (ESRS), Emotional Self Awareness Skills (ESAS), and Interpersonal Skills Scale (ISS) with the Internal Health Locus of Control (IHLOC). Doctors Health Locus of Control (DHLOC) also have significant relationship to emotional intelligence’s all sub divisions, whereas external health locus of control including Chance Health Locus of Control (CHLOC) and Powerful Other people Health Locus of Control (PHLOC) both are related to psychological distresses but it was observed in breast cancer population that chance was significantly correlated to ESAS, and ISS and powerful other people locus. Further on group comparison One Way Analysis of Variance (ANOVA) depicted no significant difference on disease stage groups. Conclusion: The strength factors of EI and HLOC are highlighted in current study. It was concluded that Emotional Intelligence (EI) and health locus of control (IHLOC, & DHLOC) have positive direction of relationship, both skills leads to positive adaptation and greater coping strengths.